Revised WIC Food Package and Children’s Diet Quality - Tester, June M. (Pediatrics, 2016)
BACKGROUND AND OBJECTIVES: In October 2009, the Special Supplemental Nutrition Program for Women, Infant, and Children (WIC) food package was revised to include more fruits, vegetables, whole grains, and lower-fat milk. We examined the impact of the WIC food package revisions on the diet quality of children in households using WIC. METHODS: A total of 1197 children aged 2 to 4 years from low-income households were studied from before and after the policy implementation (using the 2003–2008 and 2011–2012 National Health and Nutrition Examination Survey). The Healthy Eating Index–2010 (HEI-2010) was calculated using two 24-hour diet recalls. Linear regression was used to examine the difference in HEI-2010 score attributable to the food package change, adjusting for baseline and secular trends among WIC participants and nonparticipants, as well as child and household characteristics. Component scores of the HEI-2010 index were analyzed with generalized linear models. RESULTS: Average HEI-2010 scores for participants and nonparticipants were 52.4 and 50.0 at baseline, and 58.3 and 52.4 after the policy change, respectively. The WIC food package revisions were associated with an adjusted average of 3.7 additional HEI-2010 points (95% confidence interval, 0.6–6.9) for WIC participants compared with nonparticipants. In particular, the revisions were associated with a 3.4-fold relative increase (95% confidence interval, 1.3–9.4) in the Greens and Beans component score for WIC participants compared with nonparticipants. CONCLUSIONS: Results from this national sample indicate that the WIC food package revisions were associated with higher diet quality for children participating in WIC.